Analisis Effect Size Pengaruh Penerapan LKS Terhadap Hasil Belajar Siswa pada pembelajaran IPA dan Fisika - Dwi Putri Ramadhani*; Asrizal Asrizal; Festiyed Festiyed (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
In 21st century is known for its rapidly developing technology, knowledge, and skills. In 21st century education demands the creation of quality human resources. The government's effort in handling case 21st used the application of the 2013 curriculum. One of the goals of the 2013 curriculum is to improve student learning outcomes. Improving learning outcomes can be done by using learning resources form of worksheets. Currently, a lot of research is being done on the effect of student worksheets on student learning outcomes. Some studies have different results, so the results of these studies need to use the journal review method with effect size analysis. Thus the purpose of this study was to determine and compare the influence of worksheets on learning outcomes. The data technique in this research is documentation technique. The analysis technique used is quantitative analysis for value and qualitative analysis for analyzing research data. In this study uses 20 journals consisting of 6 international journals and 14 national journals. From the journal, the moderator variables are obtained, namely the level of education, subject matter, and learning models. From the results of the journal analysis of learning outcomes based on the level of education, it was found that the effect size of SMP 1.30 and SMA was 0.90. Based on the classification of science material the effect size is 1.29 and physics is 0.96. Based on the learning model, the effect size is 1.23. The conclusion is that the use of worksheets can improve student learning outcomes in science and physics learning.